2011
DOI: 10.1093/qjmed/hcq238
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of adenosine stress myocardial perfusion by cardiac magnetic resonance imaging in patients with known or suspected coronary artery disease

Abstract: In patients with known or suspected CAD, adenosine stress CMR could be used to identify patients at high risk for subsequent cardiac death or nonfatal MI. A normal CMR perfusion was associated with a very low long-term event rate and excellent long-term prognosis. In addition, stress CMR perfusion provided important incremental prognostic information over clinical risk factors and RWMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…[20][21][22][23]26,30 Of the 13 series of patients included for subanalysis using the criterion to define the test as negative, 7 used the absence of inducible PDs [20][21][22]27,[29][30][31] as the criterion to define a negative test; of these studies, 1 used dipyridamole as the stressor, 4 used adenosine, and 2 used a stress protocol with both dipyridamole and adenosine. In the remaining 6 series of patients, the definition of a negative study was based on the absence of inducible ; of these, 1 used dipyridamole and 5 used dobutamine as the stressor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23]26,30 Of the 13 series of patients included for subanalysis using the criterion to define the test as negative, 7 used the absence of inducible PDs [20][21][22]27,[29][30][31] as the criterion to define a negative test; of these studies, 1 used dipyridamole as the stressor, 4 used adenosine, and 2 used a stress protocol with both dipyridamole and adenosine. In the remaining 6 series of patients, the definition of a negative study was based on the absence of inducible ; of these, 1 used dipyridamole and 5 used dobutamine as the stressor.…”
Section: Resultsmentioning
confidence: 99%
“…20,[26][27][28][29][30] Figure 4 shows the forest plot of the NPV and ERNT for each study, as well as the pooled estimates yielded by the random-effect model (I 2 =94.7%; P<0.001). The individual NPVs ranged from 75.27% to 100%.…”
Section: Predictive Value Of Stress Cmr For Myocardial Revascularizatmentioning
confidence: 99%
“…The specificity and diagnostic accuracy of both methods were low because both MPS and Stress Echo procedures are ischemia imaging protocols and angiography as a gold standard causes increase in false positive results. However the positive ischemia finding to be an independent predictor of cardiac events according to approximately four years follow up of 203 patients in a previous study [17]. Additionally parameters obtained from cardiac MRI like adenosine stress perfusion, delayed enhancement, and left ventricular function has been observed to provide information regarding prognostification in another study [18].…”
Section: Discussionmentioning
confidence: 88%
“…A recent meta-analysis has shown that this technique has sensitivity and specificity of 91% and 81% respectively for detection of CAD in patients presenting with subacute/acute chest pain [64]. Similar to other stress modalities, a negative study has good prognostic outlook [65,66]. Jahnke et al evaluated 513 patients with a combined myocardial perfusion and Dobutamine CMR examination and report event free survival rates of 99.3% at three years in patients with a negative result as compared to 83.5% with a positive scan [53].…”
Section: Concurrent Assessment Of Perfusion and Viabilitymentioning
confidence: 99%